Development of high-performance graphene-based composites for energy storage in flexible electronic devices - Een Taryana (Jurnal Konseling dan Pendidikan, 2025)
The development of high-performance graphene-based composites for energy storage in flexible electronic devices has garnered significant attention due to the remarkable properties of graphene, including its excellent electrical conductivity, mechanical strength, and flexibility. This study focuses on the fabrication of advanced graphene-based composites aimed at enhancing the efficiency and longevity of energy storage systems integrated into flexible electronics. Various graphene derivatives, including reduced graphene oxide (rGO) and graphene oxide (GO), were combined with polymers and other nanomaterials to create composites that possess superior electrochemical performance, mechanical stability, and flexibility. The results demonstrated that these composites exhibit high energy and power densities, long cycle life, and exceptional flexibility, making them ideal candidates for energy storage devices in next-generation flexible electronics. The paper discusses the synthesis methods, material characterization, and performance evaluations of these composites in terms of their application in supercapacitors and batteries. The study also identifies key challenges and future directions for improving the scalability, cost-effectiveness, and overall performance of graphene-based energy storage solutions for flexible devices.